Phytoplankton Diversity in Midstream Region of Meenachil River, Kerala during Premonsoon and Monsoon Season - Mani, Reema Rose; Sebastian, Simimole (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The scenic beauty and rich diversity of Meenachil River in Kerala make it a valuable freshwater resource for the region. This study aimed to explore the phytoplankton diversity in the midstream region of Meenachil River in Kerala during the pre-monsoon and monsoon seasons. Five different taxonomic groups were identified, which included Chlorophyceae, Bacillariophyceae, Cyanophyceae, Euglenophyceae, and Xanthophyceae, with a total of 39 species. Chlorophyceae was found to be the most prevalent group with 18 taxa, followed by Bacillariophyceae with 11 taxa, Cyanophyceae with 7 taxa, Euglenophyceae,with 2 taxa and Xanthophyceae with 1 taxon. The study revealed that the pre-monsoon season had a higher abundance of phytoplankton with 39 species, while the monsoon season had only 27 species.This research provides important insights into the phytoplankton diversity of Meenachil River in Kerala and highlights the significance of monitoring changes in phytoplankton abundance throughout the seasons for effective water resource management. The findings of this study will be beneficial for future research on water quality management and monitoring in rivers.